A fuzzy random analysis model for seismic performance of framed structures incorporating structural and non-structural damage. - Gu, Xiaoming (Earthquake engineering & structural dynamics.)
Past earthquake experiences indicate that most buildings designed in accordance with modern seismic design codes could survive moderate to strong earthquakes; however, the financial loss due to repairing cost and the subsequent business interruption can be unacceptable. Designing building structures to meet desired performance targets has become a clear direction in future seismic design practice. As a matter of fact, the performance of buildings is affected by structural as well as non-structural components, and involves numerous uncertainties. Therefore, appropriate probabilistic approach taking into account structural and non-structural damages. The limit state for each performance level is defined as an interval of inter-storey drift ratios concerning, respectively, the non-structural and structural damage with a membership function, while the relative importance of the two aspects is reflected through the use of an appropriate cost function. To illustrate the methodology, herein the non-structural damage is represented by infill masonry walls. The probabilistic drift limits for RC components and masonry walls from the associated studies are employed to facilitate the demonstration of the proposed model in an example case study. The results are compared with those obtained using classical reliability model based on single-threshold performance definition. The proposed model provides a good basis for incorporating different aspects into the performance assessment of a building system.